Preparation and Characterization of Hemodialysis Membranes - Yaşar Mahlıçlı, Filiz; Alsoy Altınkaya, Sacide (Izmir Institute of Technology, 2007)
Hemodialysis is a widely used clinical therapy for end-stage renal failure and dialysis membranes are vital components of a hemodialysis unit. The most desirable properties of a hemodialysis membrane are high mass transfer of toxic solutes to reduce the dialysis time, blood compatibility and limited protein adsorption capacity. Protein adsorption or deposition on the surface or in its pores results in a progressive decline in flux, change of selectivity of the membrane and the activation of different defense systems in blood. To prepare hemodialysis membranes with improved transport properties and protein adsorption resistant surfaces, an enzyme immobilization technique was used. Asymmetric cellulose acetate membranes were prepared through dry phase inversion method and they were modified by blending urease enzyme directly into the casting solution. The effect of enzyme immobilization on the protein adsorption, solute transport rates and mechanical properties was investigated through static adsorption and permeation experiments, mechanical tests and structural characterization by scanning electron microscope. It was found that the solute permeation rates decreased exponentially while the maximum tensile strength of the membranes increased significantly by increasing the cellulose acetate (CA) to acetone weight fraction ratio in the membrane forming solution due to a change in the structure from porous to dense one. Modification of the CA membrane with urease immobilization increased the permeation coefficients of creatinine and uric acid by a factor of 1.2 and 1.7, respectively. Similarly, the % removal of urea from the donor compartment in 1 hour increased from 45.8% to 53.2% by using urease immobilized CA membrane. The protein adsorption capacity of the urease immobilized CA membrane was found to be 2 times lower than that of the regular CA membrane. Protein fouling on the membranes caused a decrease in the transport rates of all solutes. Due to protein fouling, the decrease in the permeation coefficients of creatinine and uric acid are 59.0% and 76.5%, respectively, through regular CA membranes. On the other hand, urease immobilization limited the decrease in the permeation rates by 39.2% and 33.4% for creatinine and uric acid, respectively. In a similar way, the rate of removal of urea through CA membrane and urease immobilized CA membrane decreased by 31.2% and 11.7%, respectively. While urease immobilization decreased the protein adsorption capacity, it did not cause any loss in mechanical strength of the membrane. These results indicate that urease immobilization can be used to improve transport properties and reduce protein adsorption capacity of the CA membranes. Urease immobilized CA membranes prepared in this study can be used as an alternative membrane in hemodialysis units.
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2007
Includes bibliographical references (leaves: 77-80)
Text in English;Abstract:Turkish and English
xiii, 82 leaves
Keywords: TP159.M4 M21 2007; Membranes (Technology); Hemodialysis